Strategi Komunikasi Pemasaran Almaz Fried Chicken Cabang Kenten Dalam Menarik Minat Konsumen Muslim Di Kota Palembang - Ferdi Taufik Kurniawan; Indri Indri; Klara Salsabila; Abdur Razzaq; M. Yudistira Nugraha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the marketing communication strategy implemented by Almaz Fried Chicken Kenten Branch in attracting Muslim consumers in Palembang City, particularly in the context of rising consumer awareness regarding global issues such as the boycott of pro-Israeli products and the growing demand for halal local products. The research employs a descriptive qualitative approach, with data collected through non-participant observation, in-depth interviews, and documentation of promotional materials and social media content used by Almaz Fried Chicken. The findings reveal that Almaz Fried Chicken applies an integrated marketing communication strategy rooted in Islamic values. This includes the delivery of messages emphasizing halal certification, Islamic ethics in service, religious-themed interior visuals, and the use of social media platforms such as Instagram and TikTok to communicate promotions and social concern. Furthermore, Almaz strengthens its relationship with the local Muslim community through loyalty programs, social collaborations, and a 5% revenue donation to Palestine. This approach fosters emotional engagement and enhances consumer loyalty. The study concludes that a marketing communication strategy designed with consideration of religious values and social issues can serve as a strong differentiating factor in building trust among Muslim consumers. Marketing communication thus functions not only as a promotional tool but also as a means to reinforce brand identity and social contribution within the Muslim community